Organic polymer containing carbonyl and imine as well as preparation method and application of organic polymer

By developing organic polymers containing carbonyl and imine, the shortcomings of traditional lithium-ion battery positive electrode materials in solvent resistance and inherent conductivity are solved, high energy density, power density and cycle stability are achieved, and wide application prospects are achieved. .

CN119463172APending Publication Date: 2025-02-18JILIN UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411778328.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Traditional lithium-ion battery positive electrode materials have shortcomings in solvent resistance and inherent conductivity, which limits the energy density, power density and cycling stability of the battery.

Method used

An organic polymer containing carbonyl and imine was developed, which has rich redox active sites, extended π conjugated structure and excellent solubility resistance. The material is prepared by chemical synthesis method, including 3,3'-dihydroxy-2,2'-binaphthalene-1,1',4,4'-tetraketone with tetraaminomonomer in a phosphoric acid medium under a nitrogen atmosphere The reaction was then subjected to suction filtration and drying to give the organic polymer.

Benefits of technology

The organic polymer material exhibits reversible lithium ion storage, high actual specific capacity, excellent cycling stability, excellent rate performance, and high energy density and power density, significantly improving the comprehensive performance of lithium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463172A_ABST
    Figure CN119463172A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion batteries, and particularly relates to an organic polymer containing carbonyl and imine as well as a preparation method and application of the organic polymer. Aiming at the problems of insufficient solvent resistance and limited inherent conductivity of a lithium ion battery positive electrode material, the invention designs and synthesizes an organic polymer with rich redox active sites and an expanded pi conjugated structure. The organic polymer containing carbonyl and imine provided by the invention has reversible lithium ion storage, relatively high actual specific capacity, excellent cycle stability, excellent rate capability and high energy density and power density. In the synthesis of the organic polymer provided by the invention, experimental raw materials are cheap and easily available, the preparation method is simple, the reaction yield is relatively high, large-scale application of the material in the field of lithium ions is facilitated, and the material has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to an organic polymer containing a carbonyl group and an imine, and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries are widely used in the field of mobile electronic devices due to their excellent comprehensive performance. At the same time, they show great application potential in fields such as electric vehicles and large-scale energy storage systems. As the core component of the battery system, the cathode material is crucial to the energy density, power density, cycle life and safety of the battery. Traditional cathode materials for lithium-ion batteries face the challenge of not being able to meet the needs of future society due to the limitations of specific capacity and structural stability. In this context, organic cathode materials have shown great potential in improving the power density, energy density and cycle stability of lithium-ion batteries due to their flexibility in molecular structure design, excellent comprehensive performance and outstanding mechanical flexibility, and have become a field of advanced battery materials that has attracted much attention. Although organic cathode materials have shown many advantages, there are still challenges in practical applications. Among them, insufficient solvent resistance and limited intrinsic conductivity have become the most prominent problems. In order to overcome these shortcomings, the study of electrode materials with superior comprehensive performance has become a development trend in the field of organic electrode materials. Summary of the invention

[0003] In view of the above problems, the present invention provides an organic polymer containing carbonyl and imine, a preparation method and its application in the field of lithium ion batteries. The organic polymer provided by the present invention has abundant redox active sites (C=O and C=N), an extended π conjugated structure and excellent solubility resistance, so that the material has the advantages of reversible lithium ion storage, high actual specific capacity, excellent cycle stability, excellent rate performance, high energy density and power density, etc., which is helpful for the material to achieve large-scale application in the field of lithium ion positive electrode materials and has broad application prospects.

[0004] The objective of the present invention is achieved through the following technical solutions:

[0005] The first aspect of the present invention provides an organic polymer containing a carbonyl group and an imine, comprising a structure shown in formula (I):

[0006]

[0007] Wherein R is one or more of the structures R1-R4,

[0008]

[0009] A second aspect of the present invention provides a method for preparing an organic polymer containing a carbonyl group and an imine, wherein the chemical synthesis reaction and steps are as follows:

[0010]

[0011] Step 1: Under a nitrogen atmosphere, 3,3'-dihydroxy-2,2'-binaphthyl-1,1',4,4'-tetraketone and tetraamino monomer are added to an organic solvent respectively, and after being dissolved, 85% by mass of phosphoric acid is added, and after stirring at room temperature for 30 minutes, the reaction system is heated and stirred for 24 hours;

[0012] Step 2: After the reaction in step 1 is completed, the reaction system is cooled to room temperature and then filtered. The filter residue is washed with an organic solvent until the filtrate is colorless and transparent. The obtained black solid is vacuum dried to obtain an organic polymer containing carbonyl and imine.

[0013] Furthermore, in the step 1, the tetraamino monomer is one of 2,3,7,8-tetraaminopyrazine-1,4,6,9-tetraone, 1,2,4,5-phenyltetramine, 2,3,5,6-tetraaminobenzoquinone and 3,3'-diaminobenzidine.

[0014] Furthermore, in step 1, the solid content of the reaction system is 1-10%, the molar ratio of 3,3'-dihydroxy-2,2'-binaphthyl-1,1',4,4'-tetraketone to tetraamino monomer is 1:(0.5-2); the molar ratio of tetraamino monomer to phosphoric acid is 1:(3.5-4).

[0015] Furthermore, the heating reaction temperature in step 1 is 90-180°C.

[0016] Furthermore, the organic solvent in step 1 and step 2 is one or more of N,N-dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide, methanol, ethanol, water, acetone, tetrahydrofuran, and N,N-dimethylacetamide.

[0017] The third aspect of the present invention provides an application of an organic polymer containing carbonyl and imine in the field of lithium ion batteries, wherein the organic polymer containing carbonyl and imine according to claim 1 is used as an active material, Super P is used as a conductive agent, and aluminum foil is used as a positive electrode collector. The active material, the conductive agent and the binder are uniformly mixed, and the mixture is uniformly coated on the collector, and dried in a vacuum environment at a temperature of 40 to 80°C for 10 to 20 hours to obtain a positive electrode sheet of a lithium ion battery; the sheet is cut into a circular sheet with a diameter of 1 cm as a positive electrode, and a lithium sheet is used as a negative electrode, and assembled into a button battery in a glove box.

[0018] Furthermore, the mass sum of the active material, the conductive agent and the binder is calculated as 100%, wherein the active material accounts for 20-60%, the conductive agent accounts for 40-80%, and the rest is the binder.

[0019] Furthermore, the binder is one or more of polyvinylidene fluoride, sodium carboxymethyl cellulose, sodium alginate or polyacrylic acid; the electrolyte used in assembling the button battery is one of LiPF6 in EC / DEC with a volume ratio of 1:1, LiTFSI in DOL / DME with a volume ratio of 1:1, LiPF6in EC / DMC with a volume ratio of 1:1 or LiPF6 in EC / DEC / DMC with a volume ratio of 1:1:1.

[0020] Beneficial effects of the present invention:

[0021] 1. The organic polymer containing carbonyl and imine provided by the present invention has reversible lithium ion storage, high practical specific capacity, excellent cycle stability, outstanding rate performance, and high energy density and power density.

[0022] 2. The experimental raw materials for the synthesis of the organic polymer containing carbonyl and imine provided by the present invention are cheap and readily available, the preparation method is simple, and the reaction yield is high, which is conducive to the large-scale application of the material in the lithium ion field and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art; obviously, the drawings described below are some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0024] Figure 1 The electron microscope images of the organic polymers prepared in Examples 1-4 of the present invention;

[0025] Figure 2 The infrared spectrum curves of the organic polymers prepared in Examples 1-4 of the present invention;

[0026] Figure 3 X-ray diffraction spectrum curves of the organic polymers prepared in Examples 1-4 of the present invention;

[0027] Figure 4 Thermogravimetric analysis test curves of the organic polymers prepared in Examples 1-4 of the present invention;

[0028] Figure 5 The organic polymer prepared in Examples 1-4 of the present invention is 0.1A g -1 Cyclic performance curve under current density;

[0029] Figure 6 This is a rate performance test diagram of the organic polymer prepared in Examples 1-4 of the present invention;

[0030] Figure 7 The organic polymer prepared in Examples 1-4 of the present invention is at 0.2 mV s -1 Cyclic voltammetry curves of

[0031] Figure 8 The organic polymer prepared in Examples 1-4 of the present invention is 1A g -1 Cyclic performance curve under current density;

[0032] Fig. 9 The electron microscope image of the organic polymer prepared in Comparative Examples 1-2 of the present invention;

[0033] Fig.10 The organic polymer prepared in Comparative Examples 1-2 of the present invention is 0.1A g -1 Cyclic performance curve under current density;

[0034] Fig.11 The polymer prepared in Comparative Examples 1-2 of the present invention is 1A g -1 Cycling performance diagram at different current densities. DETAILED DESCRIPTION

[0035] In order to make the purpose, technical effect and technical solution of the embodiment of the present invention clearer, the technical solution in the embodiment of the present invention is clearly and completely described below in conjunction with the drawings in the embodiment of the present invention; it is obvious that the described embodiment is a part of the embodiment of the present invention. Based on the embodiment disclosed in the present invention, other embodiments obtained by ordinary technicians in this field without making creative work should all fall within the scope of protection of the present invention.

[0036] Example 1

[0037] The present invention provides a method for preparing an organic polymer containing a carbonyl group and an imine, comprising the following steps:

[0038] Step 1: Under a nitrogen atmosphere, 0.4 mmol (0.1385 g) of 3,3'-dihydroxy-2,2'-binaphthyl-1,1',4,4'-tetraketone and 0.2 mmol (0.0336 g) of 2,3,5,6-tetraaminobenzoquinone were added to 17 mL of N-methylpyrrolidone, and after dissolution, 0.048 mL of 85% phosphoric acid was added. After stirring at room temperature for 30 minutes, the reaction system was heated to 180°C and stirred for 24 hours.

[0039] Step 2: After the above reaction is completed, the reaction is cooled to room temperature and directly filtered. The filter residue is washed with methanol, water and acetone multiple times until the filtrate is colorless and transparent. The obtained black solid is vacuum dried to obtain a polymer organic positive electrode material containing carbonyl and imine, with a yield of 60%. The structural formula of the target product is shown below.

[0040]

[0041] Example 2

[0042] The present invention provides a method for preparing an organic polymer containing a carbonyl group and an imine, comprising the following steps:

[0043] Step 1: Under a nitrogen atmosphere, 0.4 mmol (0.1385 g) of 3,3'-dihydroxy-2,2'-binaphthyl-1,1',4,4'-tetraketone and 0.3 mmol (0.0504 g) of 2,3,5,6-tetraaminobenzoquinone were added to 1.9 mL of N-methylpyrrolidone, and after dissolution, 0.072 mL of 85% phosphoric acid was added. After stirring at room temperature for 30 minutes, the reaction system was heated to 120°C and stirred for 24 hours.

[0044] Step 2: After the above reaction is completed, the reaction is cooled to room temperature and directly filtered. The filter residue is washed with methanol, water and acetone multiple times until the filtrate is colorless and transparent. The obtained black solid is vacuum dried to obtain a polymer organic positive electrode material containing carbonyl and imine, with a yield of 62%. The structural formula of the target product is shown below.

[0045]

[0046] Example 3

[0047] The present invention provides a method for preparing an organic polymer containing a carbonyl group and an imine, comprising the following steps:

[0048] Step 1: Under a nitrogen atmosphere, 0.4 mmol (0.1385 g) of 3,3'-dihydroxy-2,2'-binaphthyl-1,1',4,4'-tetraketone and 0.4 mmol (0.0673 g) of 2,3,5,6-tetraaminobenzoquinone were added to 10 mL of N-methylpyrrolidone, and after dissolution, 0.096 mL of 85% phosphoric acid was added. After stirring at room temperature for 30 minutes, the reaction system was heated to 140 ° C and stirred for 24 hours.

[0049] Step 2: After the above reaction is completed, the reaction is cooled to room temperature and directly filtered. The filter residue is washed with methanol, water and acetone multiple times until the filtrate is colorless and transparent. The obtained black solid is vacuum dried to obtain a polymer organic positive electrode material containing carbonyl and imine, with a yield of 80%. The structural formula of the target product is shown below.

[0050]

[0051] Example 4

[0052] The present invention provides a method for preparing an organic polymer containing a carbonyl group and an imine, comprising the following steps:

[0053] Step 1: Under a nitrogen atmosphere, 0.4 mmol (0.1385 g) of 3,3'-dihydroxy-2,2'-binaphthyl-1,1',4,4'-tetraketone and 0.8 mmol (0.1344 g) of 2,3,5,6-tetraaminobenzoquinone were added to 5.5 mL of N-methylpyrrolidone, and after dissolution, 0.192 mL of 85% phosphoric acid was added. After stirring at room temperature for 30 minutes, the reaction system was heated to 90°C and stirred for 24 hours.

[0054] Step 2: After the above reaction is completed, the reaction is cooled to room temperature and directly filtered. The filter residue is washed with methanol, water and acetone multiple times until the filtrate is colorless and transparent. The obtained black solid is vacuum dried to obtain a polymer organic positive electrode material containing carbonyl and imine, with a yield of 40%. The structural formula of the target product is shown below.

[0055]

[0056] Example 5

[0057] The present invention provides a method for preparing an organic polymer containing a carbonyl group and an imine, comprising the following steps:

[0058] Step 1: Under a nitrogen atmosphere, 0.4 mmol (0.1385 g) of 3,3'-dihydroxy-2,2'-binaphthyl-1,1',4,4'-tetraketone and 0.4 mmol (0.3 g) of 2,3,7,8-tetraaminopyrazine-1,4,6,9-tetraketone were added to 7.8 mL of N-methylpyrrolidone, and after dissolution, 0.096 mL of 85% phosphoric acid was added. After stirring at room temperature for 30 minutes, the reaction system was heated to 140 ° C and stirred for 24 hours.

[0059] Step 2: After the above reaction is completed, the reaction is cooled to room temperature and directly filtered. The filter residue is washed with methanol, water and acetone multiple times until the filtrate is colorless and transparent. The obtained black solid is vacuum dried to obtain a polymer organic positive electrode material containing carbonyl and imine, with a yield of 40%. The structural formula of the target product is shown below.

[0060]

[0061] Example 6

[0062] The present invention provides a method for preparing an organic polymer containing a carbonyl group and an imine, comprising the following steps:

[0063] Step 1: Under a nitrogen atmosphere, 0.4 mmol (0.1385 g) of 3,3'-dihydroxy-2,2'-binaphthyl-1,1',4,4'-tetraketone and 0.4 mmol (0.0545 g) of 1,2,4,5-benzenetetramine were added to 19 mL of N-methylpyrrolidone, and after dissolution, 0.096 mL of 85% phosphoric acid was added. After stirring at room temperature for 30 minutes, the reaction system was heated to 140 ° C and stirred for 24 hours.

[0064] Step 2: After the above reaction is completed, the reaction is cooled to room temperature and directly filtered. The filter residue is washed with methanol, water and acetone multiple times until the filtrate is colorless and transparent. The obtained black solid is vacuum dried to obtain a polymer organic positive electrode material containing carbonyl and imine, with a yield of 40%. The structural formula of the target product is shown below.

[0065]

[0066] Example 7

[0067] The present invention provides a method for preparing an organic polymer containing a carbonyl group and an imine, comprising the following steps:

[0068] Step 1: Under a nitrogen atmosphere, 0.4 mmol (0.1385 g) of 3,3'-dihydroxy-2,2'-binaphthyl-1,1',4,4'-tetraketone and 0.4 mmol (0.0857 g) of 3,3'-diaminobenzidine were added to 22 mL of N-methylpyrrolidone, and after dissolution, 0.096 mL of 85% phosphoric acid was added. After stirring at room temperature for 30 minutes, the reaction system was heated to 140°C and stirred for 24 hours.

[0069] Step 2: After the above reaction is completed, the reaction is cooled to room temperature and directly filtered. The filter residue is washed with methanol, water and acetone multiple times until the filtrate is colorless and transparent. The obtained black solid is vacuum dried to obtain a polymer organic positive electrode material containing carbonyl and imine, with a yield of 40%. The structural formula of the target product is shown below.

[0070]

[0071] Example 8

[0072] The present invention provides the use of the organic polymer prepared in Example 1 in the assembly of a lithium ion battery, comprising the following steps:

[0073] The organic polymer prepared in Example 1 was used as a positive electrode active material, Super P was used as a conductive agent, and aluminum foil was used as a positive electrode current collector. The active material, the conductive agent, and the binder (sodium carboxymethyl cellulose) were uniformly mixed in a mass ratio of 4:5:1, and the mixture was uniformly coated on the current collector, and dried in a vacuum environment at a temperature of 40° C. for 20 hours to obtain a positive electrode sheet for a lithium ion battery;

[0074] The electrode was cut into a circular electrode with a diameter of 1 cm as the positive electrode, the lithium sheet was used as the negative electrode, LiPF6in EC / DEC (volume ratio of 1:1) was used as the electrolyte, and button batteries were assembled in a glove box.

[0075] Example 9

[0076] The present invention provides the use of the organic polymer prepared in Example 2 in the assembly of a lithium ion battery, comprising the following steps:

[0077] The organic polymer prepared in Example 2 was used as the positive electrode active material, Super P was used as the conductive agent, and aluminum foil was used as the positive electrode current collector. The active material, the conductive agent, and the binder (sodium alginate) were uniformly mixed in a mass ratio of 5:4:1, and the mixture was uniformly coated on the current collector, and dried in a vacuum environment at a temperature of 60° C. for 16 hours to obtain a positive electrode sheet for a lithium ion battery;

[0078] The electrode was cut into a circular electrode with a diameter of 1 cm as the positive electrode, the lithium sheet was used as the negative electrode, LiPF6in EC / DMC (volume ratio of 1:1) was used as the electrolyte, and button batteries were assembled in a glove box.

[0079] Example 10

[0080] The present invention provides the use of the organic polymer prepared in Example 3 in the assembly of a lithium ion battery, comprising the following steps:

[0081] The organic polymer prepared in Example 3 was used as the positive electrode active material, Super P was used as the conductive agent, and aluminum foil was used as the positive electrode current collector. The active material, the conductive agent, and the binder (PVDF) were uniformly mixed in a mass ratio of 3:6:1, and the mixture was uniformly coated on the current collector, and dried in a vacuum environment at a temperature of 80° C. for 12 hours to obtain a positive electrode sheet for a lithium ion battery;

[0082] The electrode was cut into a circular electrode with a diameter of 1 cm as the positive electrode, the lithium sheet was used as the negative electrode, LiTFSI inDOL / DME (volume ratio of 1:1) was used as the electrolyte, and button batteries were assembled in a glove box.

[0083] Embodiment 11

[0084] The present invention provides the use of the organic polymer prepared in Example 4 in the assembly of a lithium ion battery, comprising the following steps:

[0085] The organic polymer prepared in Example 4 was used as the positive electrode active material, Super P was used as the conductive agent, and aluminum foil was used as the positive electrode current collector. The active material, the conductive agent, and the binder (polyacrylic acid) were uniformly mixed in a mass ratio of 2:7:1, and the mixture was uniformly coated on the current collector, and dried in a vacuum environment at a temperature of 80° C. for 12 hours to obtain a positive electrode sheet for a lithium ion battery;

[0086] The electrode was cut into a circular electrode with a diameter of 1 cm as the positive electrode, the lithium sheet was used as the negative electrode, LiPF6in EC / DEC / DMC (volume ratio of 1:1:1) was used as the electrolyte, and button batteries were assembled in a glove box.

[0087] Example 12

[0088] The present invention provides the use of the organic polymer prepared in Example 5 in the assembly of a lithium ion battery, comprising the following steps:

[0089] The organic polymer prepared in Example 5 was used as the positive electrode active material, Super P was used as the conductive agent, and aluminum foil was used as the positive electrode current collector. The active material, the conductive agent, and the binder (PVDF) were uniformly mixed in a mass ratio of 3:6:1, and the mixture was uniformly coated on the current collector, and dried in a vacuum environment at a temperature of 80° C. for 12 hours to obtain a positive electrode sheet for a lithium ion battery;

[0090] The electrode was cut into a circular electrode with a diameter of 1 cm as the positive electrode, the lithium sheet was used as the negative electrode, LiTFSI inDOL / DME (volume ratio of 1:1) was used as the electrolyte, and button batteries were assembled in a glove box.

[0091] Embodiment 13

[0092] The present invention provides the use of the organic polymer prepared in Example 6 in the assembly of a lithium ion battery, comprising the following steps:

[0093] The organic polymer prepared in Example 6 was used as the positive electrode active material, Super P was used as the conductive agent, and aluminum foil was used as the positive electrode current collector. The active material, the conductive agent, and the binder (PVDF) were uniformly mixed in a mass ratio of 3:6:1, and the mixture was uniformly coated on the current collector, and dried in a vacuum environment at a temperature of 80° C. for 12 hours to obtain a positive electrode sheet for a lithium ion battery;

[0094] The electrode was cut into a circular electrode with a diameter of 1 cm as the positive electrode, the lithium sheet was used as the negative electrode, LiTFSI inDOL / DME (volume ratio of 1:1) was used as the electrolyte, and button batteries were assembled in a glove box.

[0095] Embodiment 14

[0096] The present invention provides the use of the organic polymer prepared in Example 7 in the assembly of a lithium ion battery, comprising the following steps:

[0097] The organic polymer prepared in Example 7 was used as the positive electrode active material, Super P was used as the conductive agent, and aluminum foil was used as the positive electrode current collector. The active material, the conductive agent, and the binder (PVDF) were uniformly mixed in a mass ratio of 3:6:1, and the mixture was uniformly coated on the current collector, and dried in a vacuum environment at a temperature of 80° C. for 12 hours to obtain a positive electrode sheet for a lithium ion battery;

[0098] The electrode was cut into a circular electrode with a diameter of 1 cm as the positive electrode, the lithium sheet was used as the negative electrode, LiTFSI inDOL / DME (volume ratio of 1:1) was used as the electrolyte, and button batteries were assembled in a glove box.

[0099] Comparative Example 1

[0100] The present invention provides a method for preparing an organic polymer containing a carbonyl group and an imine, comprising the following steps:

[0101] Step 1: Under a nitrogen atmosphere, 0.4 mmol (0.1385 g) of 3,3'-dihydroxy-2,2'-binaphthyl-1,1',4,4'-tetraketone and 0.4 mmol (0.0673 g) of 2,3,5,6-tetraaminobenzoquinone were added to 25 mL of N-methylpyrrolidone, and after dissolution, 1.2 mL of 85% phosphoric acid was added. After stirring at room temperature for 30 minutes, the reaction system was heated to 140°C and stirred for 24 hours.

[0102] Step 2: After the above reaction is completed, the reaction is cooled to room temperature and directly filtered. The filter residue is washed with methanol, water and acetone multiple times until the filtrate is colorless and transparent. The obtained black solid is vacuum dried to obtain a polymer organic positive electrode material containing carbonyl and imine, with a yield of 60%. The structural formula of the target product is shown below.

[0103]

[0104] Comparative Example 2

[0105] The present invention provides a method for preparing an organic polymer containing a carbonyl group and an imine, comprising the following steps:

[0106] Step 1: Under a nitrogen atmosphere, 0.4 mmol (0.1385 g) of 3,3'-dihydroxy-2,2'-binaphthyl-1,1',4,4'-tetraketone and 2 mmol (0.3363 g) of 2,3,5,6-tetraaminobenzoquinone were added to 50 mL of N-methylpyrrolidone, and after dissolution, 3 mL of 85% phosphoric acid was added. After stirring at room temperature for 30 minutes, the reaction system was heated to 140 ° C and stirred for 24 hours.

[0107] Step 2: After the above reaction is completed, the reaction is cooled to room temperature and directly filtered. The filter residue is washed with methanol, water and acetone multiple times until the filtrate is colorless and transparent. The obtained black solid is vacuum dried to obtain a polymer organic positive electrode material containing carbonyl and imine, with a yield of 44%. The structural formula of the target product is shown below.

[0108]

[0109] Comparative Example 3

[0110] The present invention provides an application of the organic polymer prepared in Comparative Example 1 in the assembly of a lithium ion battery, comprising the following steps:

[0111] The organic polymer prepared in Comparative Example 1 was used as a positive electrode active material, Super P was used as a conductive agent, and aluminum foil was used as a positive electrode current collector. The active material, the conductive agent, and the binder (PVDF) were uniformly mixed in a mass ratio of 3:6:1, and the mixture was uniformly coated on the current collector, and dried in a vacuum environment at a temperature of 80° C. for 12 hours to obtain a positive electrode sheet for a lithium-ion battery;

[0112] The electrode was cut into a circular electrode with a diameter of 1 cm as the positive electrode, the lithium sheet was used as the negative electrode, LiTFSI inDOL / DME (volume ratio of 1:1) was used as the electrolyte, and button batteries were assembled in a glove box.

[0113] Comparative Example 4

[0114] The present invention provides an application of the organic polymer prepared in Comparative Example 2 in the assembly of a lithium ion battery, comprising the following steps:

[0115] The organic polymer prepared in Comparative Example 2 was used as a positive electrode active material, Super P was used as a conductive agent, and aluminum foil was used as a positive electrode current collector. The active material, the conductive agent, and the binder (PVDF) were uniformly mixed in a mass ratio of 3:6:1, and the mixture was uniformly coated on the current collector, and dried in a vacuum environment at a temperature of 80° C. for 12 hours to obtain a positive electrode sheet for a lithium-ion battery;

[0116] The electrode was cut into a circular electrode with a diameter of 1 cm as the positive electrode, the lithium sheet was used as the negative electrode, LiTFSI inDOL / DME (volume ratio of 1:1) was used as the electrolyte, and button batteries were assembled in a glove box.

[0117] Figure 1 The electron microscope images of the polymers described in Examples 1-4 of the present invention are shown. By observing the images, it can be found that the polymers present a microscopic morphology of nanoparticles of uniform size. The nanoparticle structure has a larger specific surface area, which is beneficial to increase the effective contact area between the electrolyte and the polymer. This high specific surface area can provide more ion transmission channels, thereby improving the diffusion rate of lithium ions in the electrode material and improving the rate performance of the battery. In addition, the nanoparticle structure can also shorten the diffusion path of lithium ions and reduce the charge transfer impedance.

[0118] Figure 2 The infrared test curves of the polymers described in Examples 1 to 4 of the present invention are shown in FIG. From the curves, the appearance of characteristic peaks such as C=O, C=N, CN and -NH- can be clearly observed, and the characteristic peak of -OH is not observed; the appearance of these characteristic peaks reflects the presence of specific functional groups in the polymers, which clearly confirms the successful synthesis of the polymers.

[0119] Figure 3 The X-ray diffraction spectrum curve of the polymer described in Examples 1 to 4 of the present invention shows that an obvious diffraction peak appears at 28.36°, which proves the close spatial arrangement of the aromatic rings in the polymer molecules, which helps to maintain close bonding between molecules.

[0120] Figure 4 The thermogravimetric analysis test curve of the polymer described in Examples 1-4 of the present invention. It can be observed from the figure that the polymer has good thermal stability. When the test temperature rises to 800°C, the polymer shows a higher residual carbon rate, which indicates that the polymer meets the safety standards for battery use when used as a positive electrode material.

[0121] Figure 5 The polymer described in Examples 1-4 of the present invention at 0.1A g -1 Cyclic performance diagram under current density. According to the data in the figure, the polymer as a positive electrode active material exhibits a maximum reversible specific capacity of 252.5 mA hg in a half-cell. -1 After 100 cycles, the capacity retention rate is as high as 88%. The high reversible specific capacity and excellent capacity retention rate indicate that the polymer has excellent cycle stability. This excellent cycle performance provides strong support for the application of the polymer in energy storage devices such as lithium-ion batteries.

[0122] Figure 6The figure is a rate performance test diagram of the polymers described in Examples 1-4 of the present invention. -1 ), the reversible specific capacities were 255.9, 223.2, 184, 142.2 and 101.3 mA h g -1 ; When the current density returns to 0.1A g -1 When the reversible specific capacity reaches 208.5mA hg -1 The test results clearly show that the polymer has good rate performance and reversible lithium storage capacity as a positive electrode active material.

[0123] Figure 7 The polymer described in Examples 1-4 of the present invention at 0.2 mV s -1 Cyclic voltammetry curves. From the cyclic voltammetry test results, it was observed that the half-cell corresponding to the polymer as the positive electrode active material exhibited multiple clear redox peaks, indicating that the carbonyl group and the imine group were able to undergo multi-step redox reactions; the high overlap of the curves indicated that it had highly reversible electrochemical reaction activity, and also proved that it had excellent stability during the cycle process.

[0124] Figure 8 The polymer described in Examples 1-4 of the present invention at 1A g -1 Cycling performance diagram under current density. At 1A g -1 At high current density, the half-cell corresponding to the polymer as the positive electrode active material exhibits excellent cycle stability, and its reversible specific capacity reaches 123.9 mA h g -1 , and after 1000 cycles, the capacity retention rate is as high as 95.89%. This proves the excellent electrochemical performance of the polymer as a positive electrode active material. Its excellent cycle stability and high capacity retention rate provide strong support for its reliability in high load and high power applications.

[0125] Fig. 9It is an electron microscope image of the polymer described in Comparative Examples 1-2 of the present invention. The difference between Comparative Example 1 and Examples 1-4 is that the molar ratio of the tetraamino monomer to phosphoric acid in the reaction is changed. The difference between Comparative Example 2 and Examples 1-4 is that the molar ratio of 3,3'-dihydroxy-2,2'-binaphthyl-1,1',4,4'-tetraketone to the tetraamino monomer and the molar ratio of the tetraamino monomer to phosphoric acid are changed. It can be found from the observation of the image that the microscopic morphology of the polymer is a densely stacked sheet structure, which may make it difficult for the electrolyte to penetrate between each sheet, limiting the diffusion and transmission of lithium ions. This may lead to a reduction in the effective contact area between the electrode surface and the electrolyte, thereby affecting the insertion and extraction rate of lithium ions in the electrode material and reducing the charge and discharge efficiency of the battery. In addition, due to the close stacking of the sheet structure, the interfacial reaction between the electrolyte and the electrode material may increase. These interfacial reactions may cause the electrolyte to decompose and the solid-liquid interface impedance to increase, thereby reducing the cycle stability and long-term safety of the battery.

[0126] Fig.10 The organic polymer prepared in Comparative Examples 1-2 of the present invention is 0.1A g -1 Cyclic performance diagram under current density. The button cells assembled in Comparative Examples 3-4 use the organic polymer prepared in Comparative Examples 1-2 as the positive electrode material. The observation results show that the prepared organic polymer positive electrode material containing carbonyl and imine exhibits a higher specific capacity in the initial discharge stage, which is 219.9 mA hg -1 and 245.4mA hg -1 However, as the number of cycles increases, the specific capacity continues to decrease and cannot remain stable. The root cause of this phenomenon is the change in the molar ratio of tetraamino monomer to phosphoric acid, which leads to a lower molecular weight of the two organic polymer cathode materials; during the cycle, they continue to dissolve, resulting in a decrease in specific capacity.

[0127] Fig.11 The organic polymer prepared in Comparative Examples 1-2 of the present invention is 1A g -1 Cycling performance diagram under current density. The button cells assembled in Comparative Examples 3-4 use the organic polymer prepared in Comparative Examples 1-2 as the positive electrode material. The observation results show that the long-cycle performance of the organic polymer positive electrode material containing carbonyl and imine prepared in Comparative Examples 3-4 is poor, and the specific capacity drops significantly at the beginning of the cycle. After 1000 cycles, the capacity retention rates are only 44% and 37%, respectively; in addition, the coulombic efficiency deviates significantly from 100% during the cycle, which indicates the insufficiency of the electrochemical redox reaction kinetics and reversibility of the material.

[0128] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the same. Although the present invention has been described in detail with reference to the above embodiments, a person skilled in the art can still modify or make equivalent substitutions to the specific implementations of the present invention. Any modifications or equivalent substitutions that do not depart from the spirit and scope of the present invention are within the scope of protection of the claims of the present invention to be approved.

Claims

1. An organic polymer containing a carbonyl group and an imine, characterized in that: Including the structure shown in formula (I): Wherein R is one or more of the structures R1-R4, 2. The method for preparing an organic polymer containing a carbonyl group and an imine according to claim 1, characterized in that: The following steps are involved: Step 1: Under a nitrogen atmosphere, 3,3'-dihydroxy-2,2'-binaphthyl-1,1',4,4'-tetraketone and tetraamino monomer are added to an organic solvent respectively, and after being dissolved, 85% by mass of phosphoric acid is added, and after stirring at room temperature for 30 minutes, the reaction system is heated and stirred for 24 hours; Step 2: After the reaction in step 1 is completed, the reaction system is cooled to room temperature and then filtered. The filter residue is washed with an organic solvent until the filtrate is colorless and transparent. The obtained black solid is vacuum dried to obtain an organic polymer containing carbonyl and imine.

3. The method for preparing an organic polymer containing carbonyl and imine according to claim 2, characterized in that: The tetraamino monomer in step 1 is one of 2,3,7,8-tetraaminopyrazine-1,4,6,9-tetraone, 1,2,4,5-phenyltetramine, 2,3,5,6-tetraaminobenzoquinone and 3,3'-diaminobenzidine.

4. The method for preparing an organic polymer containing carbonyl and imine according to claim 2, characterized in that: The solid content of the reaction system in step 1 is 1-10%, and the molar ratio of 3,3'-dihydroxy-2,2'-binaphthyl-1,1',4,4'-tetraketone to tetraamino monomer is 1:(0.5-2); The molar ratio of the tetraamino monomer to phosphoric acid is 1:(3.5-4).

5. The method for preparing an organic polymer containing carbonyl and imine according to claim 2, characterized in that: The heating reaction temperature in step 1 is 90-180°C.

6. The method for preparing an organic polymer containing carbonyl and imine according to claim 2, characterized in that: The organic solvent in step 1 and step 2 is one or more of N,N-dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide, methanol, ethanol, water, acetone, tetrahydrofuran, and N,N-dimethylacetamide.

7. Use of the organic polymer containing carbonyl and imine according to claim 1 in the field of lithium ion batteries.

8. The use of an organic polymer containing carbonyl and imine in the field of lithium ion batteries according to claim 7, characterized in that: The organic polymer containing carbonyl and imine as claimed in claim 1 is used as an active material, Super P is used as a conductive agent, and aluminum foil is used as a positive electrode current collector. The active material, the conductive agent and the binder are uniformly mixed, and the mixture is uniformly coated on the current collector, and dried in a vacuum environment at a temperature of 40 to 80° C. for 10 to 20 hours to obtain a positive electrode sheet for a lithium ion battery; The electrode was cut into a circular electrode with a diameter of 1 cm as the positive electrode, and the lithium sheet was used as the negative electrode, and assembled into a button battery in a glove box.

9. The use of an organic polymer containing carbonyl and imine in the field of lithium ion batteries according to claim 8, characterized in that: The mass sum of the active material, the conductive agent and the binder is calculated as 100%, wherein the active material accounts for 20-60%, the conductive agent accounts for 40-80%, and the rest is the binder.

10. The use of an organic polymer containing carbonyl and imine in the field of lithium ion batteries according to claim 8, characterized in that: The binder is one or more of polyvinylidene fluoride, sodium carboxymethyl cellulose, sodium alginate or polyacrylic acid; The electrolyte used in assembling the button battery is one of LiPF6 in EC / DEC with a volume ratio of 1:1, LiTFSI in DOL / DME with a volume ratio of 1:1, LiPF6 in EC / DMC with a volume ratio of 1:1, or LiPF6 in EC / DEC / DMC with a volume ratio of 1:1:1.

Citation Information

Cited By

  • Conjugate extended lithium-containing organic positive electrode material and preparation method and application thereof

    CN120329544A